Becoming bilingual on early childhood - Puhl, Telma da Costa (BELT - Brazilian English Language Teaching Journal, 2011)
Being bilingual is something that has intrigued people nowadays. People have been worried about speaking a second language and want their children to learn another language in a more natural way. Therefore, exposing them to more than one language on early childhood might be more efficient. From this point of view, this article aims at researching a little more about bilingualism and children who become bilingual very early. First of all, it will present a review of the literature on bilingualism itself. After, it will present some advantages of the acquisition of a second language while being a child and also some myths about second language learning . The conclusion is that children that learn two or even more languages, at the same time, learn as if they were all their first languages and they are also able to alternate languages whenever they think it’s adequate. Moreover, bilingual acquisition leads to the same kind of grammatical competence of monolingual first language development.